2017
DOI: 10.1016/j.fsigss.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Efficiencies of recovery and extraction of trace DNA from non-porous surfaces

Abstract: 13DNA recovery and extraction efficiencies are key considerations for trace DNA 14 interpretation in casework, but prior studies have tended to focus on assessing these 15 for body fluids rather than trace DNA. This study therefore examined the recovery and 16 extraction of trace DNA using different collection methods from a range of non-porous 17 surfaces relevant to crimes including homicides, terror attacks, and wildlife poaching. 18 Direct extraction of DNA from solutions of a known concentration revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 8 publications
4
37
1
Order By: Relevance
“…The main methodologies applied are swabbing, tape lifting or direct extraction via excision [7,211]. There are however many types of swabs and tape-lifts, and means of their application, with significant differences in retrieval rates [7,[212][213][214][215][216][217][218][219][220][221]. Some other methods are available such as a wet-vacuum system [222] or sampling of individual skin flakes [167], but these are less commonly utilised.…”
Section: Impact Of Different Recovery Methodologiesmentioning
confidence: 99%
“…The main methodologies applied are swabbing, tape lifting or direct extraction via excision [7,211]. There are however many types of swabs and tape-lifts, and means of their application, with significant differences in retrieval rates [7,[212][213][214][215][216][217][218][219][220][221]. Some other methods are available such as a wet-vacuum system [222] or sampling of individual skin flakes [167], but these are less commonly utilised.…”
Section: Impact Of Different Recovery Methodologiesmentioning
confidence: 99%
“…In Wood et al [4], an extraction efficiency around 81% was reported, using QIAamp® DNA Investigator Kit (QIAGEN). This is higher than those reported in this paper: 23% and 63%, using respectively, QIAshredder-QIAamp DNA Mini kit and Investigator® Lyse&Spin Basket-QIAamp DNA Mini kit.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the direct comparison between them has its limits. Indeed in Wood et al [4], acellular DNA was used whereas keratinocyte cells were used in this study. DNA traces, obtained when touching a surface may be the results of a mix between acellular DNA, and cells [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations